Adherence to the Mediterranean diet is an independent predictor of circulating vitamin D levels in normal weight and non-smoker adults: an observational cross-sectional study. (18th August 2021) - Dalamaga, Maria; Muscogiuri, Giovanna; Paganitsa, Georgia; Parvouleskou, Georgeta; Syriou, Vassiliki; Karagkoynis, Panagiotis; Stratigou, Theodora; Vallianou, Natalia; Christodoulatos, Gerasimos Socrates; Karampela, Irene; Daskalopoulou, Konstantina
Abstract: We explored the association between circulating 25OHD and adherence to the Mediterranean Diet (MedDiet) in 402 Greek (21–65 years, 188 men and 214 women), normal weight, non-smoker, healthy volunteers in the Athens metropolitan area during summer and autumn, taking into account skin phototype, anthropometric, and lifestyle variables. Circulating 25OHD, parathormone, creatinine, calcium, and phosphate were determined. A vitamin D status of ≤25, ≤50, and ≤75 nmol/L was observed in 4.5, 37.3, and 74.1% of the subjects, respectively. The independent predictors of 25OHD deficiency were autumn, darker skin phototype, BMI, or waist circumference (WC), sunscreen use, less physical outdoor activity, and less adherence to the MedDiet. Higher intake of fish and olive oil was a positive independent predictor of elevated circulating 25OHD levels. In conclusion, higher adherence to the MedDiet, fish and olive oil consumption, were positively associated with circulating 25OHD independently from BMI or WC, skin phototype, season, and physical activity.